The effectiveness of using distance learning from the viewpoint of secondary school teachers in the period of the Corona pandemic – A comparative study between the Hashemite Kingdom of Jordan and the Syrian Arab Republic – - Ibdah, Alaa Fareed (Journal of Educational and Psychological Sciences, 2020)
The aim of the study is to explore the effectiveness of distance learning from the viewpoint of high school teachers in the educational process in the Hashemite Kingdom of Jordan and the Syrian Arab Republic within the Corona pandemic, and study the significance of differences in the effectiveness of distance learning according to the gender variable, specialization and years of experience. To achieve the goals of the study, the researcher prepared a questionnaire to survey the views of teachers about the effectiveness of distance learning and prepare it electronically, and applied it to a random sample consisting of (300) teachers and schools in the Hashemite Kingdom of Jordan in Irbid Governorate, and (300) teachers and schools in the Syrian Arab Republic in Aleppo Governorate. Results showed: The effectiveness of distance learning in the Corona pandemic period was lower than the average for the study sample, There are statistically significant differences in the extent of the effectiveness of distance learning in the educational process due to the state factor and to the Hashemite Kingdom of Jordan, There are statistically significant differences in the effectiveness of distance learning in the educational process due to the sex factor and in favor of females, There are statistically significant differences in the extent of the effectiveness of distance learning in the educational process due to the specialty factor and in favor of theoretical major, There are statistically significant differences in the effectiveness of distance learning in the educational process due to the factor of years of experience in favor of (from 5 to 10 years) followed by (less than 5 years) and then (more than 10 years).